[Glycosphingolipids Gb3 and iGb3. In vivo roles in hemolytic-uremic syndrome and iNKT cell function]. - Porubsky, S; Luckow, B; Bonrouhi, M; Speak, A; Cerundolo, V; Platt, F; Gröne, H (2008)
UNLABELLED: The glycosphingolipids globotrihexosylceramide (Gb3, CD77) and isoglobotrihexosylceramide (iGb3) are isomers differing only in one glycosidic bond and have been implicated in several processes of the innate and adaptive immune system. AIMS: 1) To verify the function of Gb3 in the pathogenesis of hemolytic-uremic syndrome as the cellular receptor responsible for cytotoxicity caused by verotoxin (VT) elaborated by Shigella and certain strains of E.coli. 2) To investigate in vivo the previously implicated function of iGb3 as the endogenous lipid ligand responsible for positive selection of invariant natural killer T-cells (iNKT), which have an essential regulatory function in infection, tumor rejection and tolerance. METHODS: Generation of mice deficient in Gb3 and iGb3 synthesizing enzymes and VT injection into Gb3-deficient mice. Analysis of iNKT cell development and function by flow cytometry and by administration of the exogenous agonist alpha-galactosylceramide in iGb3-deficient mice. RESULTS: For 1) Gb3-deficient mice were insensitive to otherwise lethal doses of VT, and 2) iGb3-deficient mice showed normal numbers of iNKT cells. Furthermore the function of iNKT cells evolving in iGb3-deficient mice was unaffected. CONCLUSIONS: 1) Gb3 is the cellular receptor mediating verotoxin cytotoxicity in haemolytic-uremic syndrome. 2) In contrast to previous indirect implications, iGb3 cannot be regarded as an endogenous ligand responsible for the positive selection of iNKT cells.